INTEGRASI KEILMUAN DALAM KONTEKS TRANSDISIPLINER PADA PENDIDIKAN ISLAM KONTEMPORER: SEBUAH KAJIAN SYSTEMATIC LITERATURE REVIEW (SLR) - Tria Yuanita; Agus Zaenul Fitri (STKIP Pesisir Selatan, 2026)
The integration of science in Islamic education is a strategic issue in responding to thecomplexity of scientific, social, and cultural challenges in contemporary society. Thedynamics of the study indicate a paradigm shift from multidisciplinary andinterdisciplinary approaches to a more holistic, integrative, and contextualtransdisciplinary approach. This study aims to systematically examine thecharacteristics of transdisciplinary-based scientific integration, its theoretical andpractical contributions, and the various challenges of its implementation in Islamiceducation. The method used is a Systematic Literature Review (SLR) by adopting theKitchenham model, which includes the planning, conducting, and reporting stages.The literature search process was conducted through the Google Scholar database withthe help of the Publish or Perish application for publications from 2020–2025. Of thetotal 200 articles identified, 30 articles were declared to meet the inclusion, exclusion,and quality assessment criteria for further analysis. The results show that theintegration of transdisciplinary science in Islamic education has key characteristics inthe epistemological, conceptual, and methodological dimensions. This approach makesa significant contribution to reconstructing the epistemology of Islamic education anddeveloping a more integrative and contextual curriculum and learning environment.However, its implementation still faces paradigmatic, pedagogical, and institutionalchallenges that require strengthening the implementation model and supporting ongoing empirical research